2014
DOI: 10.1179/1476830513y.0000000100
|View full text |Cite
|
Sign up to set email alerts
|

The common polymorphism Val109Asp in the omentin gene is associated with daily energy intake in the Central-European population

Abstract: This is, so far, the first study to investigate the polymorphisms in the omentin gene in a large population cohort of obese and non-obese individuals. Based on our results, the rs2274907 polymorphism is associated with the daily energy intake as well as daily intake of fat and protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
4
18
0
3
Order By: Relevance
“…In these studies the polymorphism Val109Asp was the most frequently analyzed. The results of these studies demonstrated an association between the TT genotype and a lower energy-supplemented diet and the AA genotype and higher energy content of meals (29). In other studies, no relationship was confirmed between the analyzed polymorphism and the development of osteoporosis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In these studies the polymorphism Val109Asp was the most frequently analyzed. The results of these studies demonstrated an association between the TT genotype and a lower energy-supplemented diet and the AA genotype and higher energy content of meals (29). In other studies, no relationship was confirmed between the analyzed polymorphism and the development of osteoporosis.…”
Section: Discussionmentioning
confidence: 94%
“…There have been many studies that explore the relationship between gene polymorphism of omentin and occurrence of some diseases such as eating disorders and obesity (29), diabetes (30), heart disease (31), acne (32), and bowel disease (30). In these studies the polymorphism Val109Asp was the most frequently analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…В настоящее время исследований по оценке распределений вариантов полиморфизма Val109Asp гена оментина в различных азиатских и европейских популяциях немного. Тем не менее, по имеющимся немногочисленным литературным данным, частота встречаемости минорного аллеля Val маркера Val109Asp гена оментина у иранцев составляет 0,18 [16], у турков -0,22 [17], у чехов -0,30 [18], у американцев -0,31 [12]. В кыргызской популяции частота встречаемости минорного аллеля Val составила 0,26.…”
Section: Discussionunclassified
“…В доступной научной литературе имеются единичные исследования, касающиеся ассоциативных связей полиморфного локуса Val109Asp гена оментина с различными компонентами МС, в том числе и с АО. В 2015 г. опубликована работа, показавшая ассоциацию локуса Val109Asp гена оментина с развитием АО у чехов [18]. При исследовании чешской популяции пациенты с ожирением и без ожирения по частоте встречаемости генотипов и аллелей полиморфного маркера Val109Asp гена оментина существенно не отличались.…”
Section: Discussionunclassified
See 1 more Smart Citation